Regional Issues, Banking Reform and Related Credit Risk in Russia - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2003)
The last decade of the past century has been dominated by growing decentralization in Russia, both in economic and political terms. The major factors driving decentralization were the weakness of the federal government and of President Yeltsin, as well as the poor performance of the federal budget. As a consequence of decentralization, economic policy in Russia was increasingly determined at the regional level, resulting in economic fragmentation and in numerous barriers to the movement of goods and production factors. Although the economic upturn and the relative political stability which returned to the country with the election of President Putin have halted the separatist regional trends, interregional economic barriers are still substantial. The enormous disparities across Russian regions observed nowadays are partly linked to the inherited economic structure and the varying ability of different branches to respond to the shocks of transition, but also to the policies pursued by the regional administrations. On the one hand, raw materials extraction and exporting continue to bring most revenues, benefiting the few richly endowed regions. On the other hand, whereas in many areas of central Russia a still unreformed and uncompetitive manufacturing sector (including defence production) is a major factor behind depressed incomes, some regions have been relatively successful in their restructuring efforts, often via creating an attractive investment environment. The 'core' area in terms of attractiveness for investors includes the axis Moscow - St. Petersburg, as well as the axis stretching from Moscow eastwards. Over the period following the 1998 crisis, the Russian banking sector has recovered substantially, with assets, market capitalization, and the volumes of both deposits and loans all rising in real terms. However, banking assets still correspond to just 39% of GDP - much below the levels observed in most Central European transition countries. The banks' capitalization of 6% of GDP, the volume of credit to the real economy of 15% of GDP, and the volume of household deposits of 10% of GDP are all signs of the sector's under-development. The bulk of loans is extended to raw materials' exporters, whereas smaller enterprises' access to credit is often restricted. In addition, the role of bank loans in financing fixed capital investment is negligible. All this points to the inability of the banking sector to provide efficient financial intermediation in Russia. On the one hand, this is due to the narrow deposit base - a legacy of the 1998 crisis and the long-standing capital flight, which may have resulted in a cumulated outflow of some USD 250-300 billion. Most households still prefer to keep their savings in foreign cash, although the developments of recent months could be interpreted as a sign of a possibly coming turnaround. Also, it is hoped that the implementation of a deposit insurance scheme starting from 2005 will be helpful in attracting private deposits. On the other hand, lending is constrained by the numerous legislative and regulatory deficiencies, such as the impossibility to enforce a collateral, the cumbersome regulations accompanying lending to small businesses, the absence of credit bureaus, etc. Although the Central Bank seems to be committed to enacting the necessary changes and has elaborated a comprehensive programme of reforms accompanied by a strengthening of the banking supervision, this is not going to be a smooth process. In particular, the planned transition to IAS will entail a number of problems. Besides, although the state will probably succeed in selling off its numerous stakes, the sector will remain uncompetitive as long as Sberbank, which now accounts for 67% of private deposits and is the only bank present in all Russian regions, dominates. In Russian circumstances, a way to encourage competition is to promote the consolidation of the more than 1300 banks, most of which are tiny and essentially represent treasuries of affiliated industrial enterprises. The interest of foreign banks to enter the Russian market seems to be limited so far, notwithstanding several liberalization measures undertaken recently. Disagreement over the degree of openness of the banking sector remains, along with the level of prices of energy, a major stumbling block in Russia's WTO negotiations.
Keywords: G2; O5; P2; R1; 330; financial sector; regional economics; transitional economies; country study; regional credit ratings; fiscal federalism; banking reform